Distribution characteristics and exploration and development prospects of coalbed methane resources in Sinopec - Dehua ZHOU; Gang CHEN; Shihu ZHAO; Baojian SHEN; Zengqin LIU; Jincheng YE; Xinjun CHEN; Jiaqi ZHANG (Meitan kexue jishu)
Exploration breakthroughs of deep coalbed methane (CBM) in the Ordos Basin have driven rapid industry development since 2019. Based on the characteristics of complex coalbed methane (CBM) resource types and strong spatial heterogeneity of reservoir attributes in Sinopec's exploration areas, this study systematically conducts CBM resource evaluation and distribution characteristics research through a three-tiered progressive evaluation process encompassing “typical block analysis-parameter system construction-regional extrapolation and application”, aiming to accelerate Sinopec’s CBM industry growth and optimize exploration strategies. Key findings include: ① Sinopec’s exploration areas contain 10.31 × 1012 m3 of geological CBM resources (burial depth<4000 m), with 3.07 × 1012 m3 recoverable, primary distributed in the Ordos, southern Sichuan-northern Guizhou, Junggar, Bohai Bay, and eastern Yunnan-western Guizhou basins; ② 7.69 × 1012 m3 (74.6% of total resources) are located in mountainous, desert, and loess plateaus terrains, significantly increasing exploration and development complexity; ③ Mid to high rank coals host 8.95 × 1012 m3 (86.9% of total resources), predominantly in the Ordos, southern Sichuan-northern Guizhou, Bohai Bay, and eastern Yunnan-western Guizhou basins; ④ Deep CBM (burial depth>1 500 m) shows high exploration potential, with a geological resource of 7.59 × 1012 m3 (73.6% of total resources), inluding 6.95 × 1012 m3 from mid to high rank coals concentrated in the Ordos and the southern Sichuan-northern Guizhou basins; ⑤ Sustained fundamental research, prioritized core technology development, differentiated exploitation strategies, and deep CBM industrial base construction are critical for industry advancement. The above findings provide a scientific foundation for Sinopec’s CBM strategic planning while establishing a replicable framework for CBM exploration in other regions.